Rancangan Modul Ajar Kurikulum Merdeka Berbasis Pendekatan Kontekstual Untuk Meningkatkan Kecakapan Komunikasi Matematis - Essy Puspita Rahim; Maimunah Maimunah; Nahor Hutapea (Media Pendidikan Matematika, 2026)
This study aims to develop a teaching module based on the contextual approach on the topic of relations and functions to enhance the mathematical communication skills of students in Phase D. The novelty of this module lies in the explicit integration of contextual approach components with mathematical communication indicators, including the ability to express ideas verbally, symbolically, through tables, and graphically in a structured manner in accordance with Phase D learning outcomes, and is designed to support student-centered learning and reinforce the Pancasila Student Profile as a key characteristic of the Merdeka Curriculum. This study is a Research and Development (R&D) study using the 4-D model, which includes the define, design, develop, and disseminate stages, though it is limited to the develop stage. The research instrument consists of a validation sheet to assess the module’s feasibility. The evaluation results from three validators showed an average score of 3.57 with a percentage of 89.33% in the “highly valid” category. These findings indicate that teaching modules developed systematically with the integration of a contextual approach have the potential to support the improvement of students’ mathematical communication skills in the topics of relations and functions and are relevant to the learning characteristics of the Merdeka Curriculum. Practically, this module can be used as an alternative learning tool to help teachers facilitate more meaningful and contextual learning, while academically, the results of this study contribute to the development of contextual approach-based teaching materials for mathematics learning in Phase D.